Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18031350
|View full text |Cite
|
Sign up to set email alerts
|

Stunting as a Synonym of Social Disadvantage and Poor Parental Education

Abstract: Socially, economically, politically and emotionally (SEPE) disadvantaged children are shorter than children from affluent background. In view of previous work on the lack of association between nutrition and child growth, we performed a study in urban schoolchildren. We measured 723 children (5.83 to 13.83 years); Kupang, Indonesia; three schools with different social background. We investigated anthropometric data, clinical signs of malnutrition, physical fitness, parental education, and household equipment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
(40 reference statements)
0
20
0
5
Order By: Relevance
“…34 However, it should be noted that developmental delay be a sign of social disadvantage and may not be totally attributable to malnutrition (stunting). 27,28 Evidence showed that stunting is not a significant factor associated with the risk of developmental delay (AOR=1.36; 0.85, 2.15) or low development (AOR=0.92; 0.48, 1.78). 26 This might opt to search for potential underlying causes of developmental delay related to aflatoxin exposure, social disadvantage and other potentially interacting factors hindering children development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 However, it should be noted that developmental delay be a sign of social disadvantage and may not be totally attributable to malnutrition (stunting). 27,28 Evidence showed that stunting is not a significant factor associated with the risk of developmental delay (AOR=1.36; 0.85, 2.15) or low development (AOR=0.92; 0.48, 1.78). 26 This might opt to search for potential underlying causes of developmental delay related to aflatoxin exposure, social disadvantage and other potentially interacting factors hindering children development.…”
Section: Discussionmentioning
confidence: 99%
“…26 This might opt to search for potential underlying causes of developmental delay related to aflatoxin exposure, social disadvantage and other potentially interacting factors hindering children development. 27,28 Multipronged stunting prevention strategies, such as ensuring food security, improving caregiver knowledge and understanding, and providing proper health care, should be strengthened to ensure long-term achievement of optimal child development. Hence, holistic nurturing care covering the nutritional, social, and psychological aspects of children's lives is critical to halting the bad cycle of poverty, malnutrition, and economic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that height trajectories are highly variable across countries, which indicates heterogeneous health advantages [ 52 ]. Parental education, a socioeconomic determinant, has been associated with both stunting and dietary intake patterns, and was therefore considered relevant in the context of the dietary patterns and height relations [ 53 ]. Finally, we analyzed fruit and vegetables both combined and separately.…”
Section: Discussionmentioning
confidence: 99%
“…According to a 2006 study by the Population Council, only 39% of Maya women are literate compared to 77% Ladino women, 68% of Maya men, and 87% Ladino men (https://knowledgecommons.popcouncil.org/cgi/viewcontent.cgi?article=1057%26context=departments_sbsr-pgy). Poverty, social disadvantage, gender inequality, number of years of schooling, literacy, and related education variables are often the strongest correlates of human growth in height (Scheffler et al, 2021). For more than a century in Guatemala, the upstream governmental policies of systematic under‐funding for Maya education have maintained intergenerational cycles of inequality and the stagnation of Maya growth in height.…”
Section: Inequality Violence and Gender In Guatemalamentioning
confidence: 99%